Linear discrete pursuit game problem with total constraints - Kuchkarov, Atamurat; Ibragimov, Gafurjan; Sotvoldiev, Akmal (Hindawi Publishing Corporation, 2013)
We study a linear discrete pursuit game problem of one pursuer and one evader. Control vectors of the players are subjected to total constraints which are discrete analogs of the integral constraints. By definition pursuit can be completed in the game if there exists a strategy of the pursuer such that for any control of the evader the state of system z(t) reaches the origin at some time. We obtain sufficient conditions of completion of the game from any initial position of the state space. Strategy of the pursuer is defined as a function of the current state of system and value of control parameter of the evader.